Pineapple peel industry determination with weighted location method - Nu’man, A H; Nurwandi, L; Bahtiar, I; Omar, Salmah (IOP Publishing Ltd, 2020)
This study discusses alternative fuels to replace gasoline with bioethanol. Bioethanol can be produced including pineapple, where the peel can be used to be converted into bioethanol instead of gasoline. The use of pineapple peel for small-scale production in this study was the main focus, so that the community would get benefit from the economic value. The community to use pineapple peel is the main concern, to get information about the capacity of an area. Measurement of capacity is carried out by taking into account transportation, raw material, land, energy, labour, waste, and market factors. The assessment was carried out on five zones of pineapple farming using analytical hierarchy process (AHP). Each area is determined by its coordinates, then multiplied by the weight of each region produced. The calculation results show that the determination of area was chosen to be a smallscale bioethanol production area concerning with dependent on the policy, raw materials, and transportation factor, it show that policy factor must be exist to support the operation of bioethanol industry with pineapple peels material.